2009
DOI: 10.1007/s11244-009-9275-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level Modeling of Silica–Template Interactions During Initial Stages of Zeolite Synthesis

Abstract: Zeolite synthesis is driven by structure-directing agents, such as tetrapropyl ammonium ions (TPA ? ) for Silicalite-1 and ZSM-5. However, the guiding role of these organic templates in the complex assembly to highly ordered frameworks remains unclear, limiting the prospects for advanced material synthesis. In this work, both static ab initio and dynamic classical modeling techniques are employed to provide insight into the interactions between TPA ? and Silicalite-1 precursors. We find that as soon as the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 90 publications
1
24
0
Order By: Relevance
“…Some of the observations made by Lewis et al 74 were later confirmed by Verstraelen et al 82 in a multi-level modeling study on the silica-template interactions during the initial stages of zeolite synthesis. Both static ab initio and classical MD studies were performed to obtain insight into the interactions between the tetrapropylammonium ions (TPA+) and silicalite-1 precursors.…”
Section: Modeling As a Tool In Template Designmentioning
confidence: 72%
“…Some of the observations made by Lewis et al 74 were later confirmed by Verstraelen et al 82 in a multi-level modeling study on the silica-template interactions during the initial stages of zeolite synthesis. Both static ab initio and classical MD studies were performed to obtain insight into the interactions between the tetrapropylammonium ions (TPA+) and silicalite-1 precursors.…”
Section: Modeling As a Tool In Template Designmentioning
confidence: 72%
“…In one class of models, the precursor nanoparticle framework is unrelated to that of the final zeolite. The group of Lobo proposed a detailed model in which nanoparticles consist of an unstructured silica-rich core surrounded by a TPA-rich shell [15][16][17]. This would imply a rather unspecific template role limited to change of solvent properties.…”
Section: Zeolite Synthesismentioning
confidence: 99%
“…These observations also were corroborated by theoretical studies where a clear preference of the template molecule towards Silicalite-1 fragments was derived. [16] Such a scenario implies the TPA has, asides the solvent structuring at early stages in the synthesis, also a direct structure directing effect on molecular level.…”
Section: Zeolite Synthesismentioning
confidence: 99%
See 2 more Smart Citations